Development of E-Worksheet Based on STEAM-PjBL in Reaction Rate Material to Improve Creative Thinking Skills High School Student - Rr Tasya Noor Nabila; Agus Kamaludin (Jurnal Iqra': Kajian Ilmu Pendidikan, 2023)
The lack of creative thinking skills causes students to be less optimal in facing challenges in the era of the industrial revolution 4.0. Therefore, efforts are needed to improve students' creative thinking skills through the learning process in the classroom. This study aims to develop and determine the quality of E-Worksheet loaded with STEAM-PjBL on reaction rate material to improve students' creative thinking skills. Research conducted using 4D models (Define, Design, Development, and Disseminate). The instrument used is in the form of product quality assessment sheets and student responses. The results of the E-Worksheet assessment based on the assessment of material experts, media experts, reviewers, and student responses received an ideal percentage of 93%, 97%, 90%, and 93% in the excellent category. Based on the assessment results,  the developed E-Worksheet can be used as an alternative learning medium to improve students' creative thinking skills.